Association of oral bisphosphonates with cardioembolic ischemic stroke: a nested case-control study - Rodríguez-Martín, Sara; Barreira-Hernández, Diana; Mazzucchelli, Ramón; Gil, Miguel; García-Lledó, Alberto; Izquierdo-Esteban, Laura; Pérez-Gómez, Ana; Rodríguez-Miguel, Antonio; De Abajo, Francisco J. (Frontiers in Pharmacology, 2023)
Background: Bisphosphonates have been reported to increase the risk of atrial fibrillation. Therefore, it is conceivable that they may increase the risk of cardioembolic ischemic stroke (IS). However, most epidemiological studies carried out thus far have not shown an increased risk of IS, though none separated by the main pathophysiologic IS subtype (cardioembolic and non-cardioembolic) which may be crucial. In this study, we tested the hypothesis that the use of oral bisphosphonates (oBs) increases specifically the risk of cardioembolic IS, and explored the effect of treatment duration, as well as the potential interaction between oBs and calcium supplements and anticoagulants. Methods: We performed a case-control study nested in a cohort of patients aged 40-99 years, using the Spanish primary healthcare database BIFAP, over the period 2002-2015. Incident cases of IS were identified and classified as cardioembolic or non-cardioembolic. Five controls per case were randomly selected, matched for age, sex, and index date (first recording of IS) using an incidence-density sampling. The association of IS (overall and by subtype) with the use of oBs within the last year before index date was assessed by computing the adjusted odds ratios (AOR) and their 95%CI using a conditional logistic regression. Only initiators of oBs were considered. Results: A total of 13,781 incident cases of IS and 65,909 controls were included. The mean age was 74.5 (SD±12.4) years and 51.6% were male. Among cases, 3.15% were current users of oBs, while among controls they were 2.62%, yielding an AOR of 1.15 (95% CI:1.01-1.30). Of all cases, 4,568 (33.1%) were classified as cardioembolic IS (matched with 21,697 controls) and 9,213 (66.9%) as non-cardioembolic IS (matched with 44,212 controls) yielding an AOR of 1.35 (95%CI:1.10-1.66) and 1.03 (95%CI: 0.88-1.21), respectively. The association of oBs with cardioembolic IS was clearly duration-dependent (AOR≤1year=1.10; 95%CI:0.82-1.49; AOR>1-3years=1.41; 95%CI:1.01-1.97; AOR>3years=1.81; 95%CI:1.25-2.62; p for trend=0.001) and completely blunted by anticoagulants, even in long-term users (AOR>1year=0.59; 0.30-1.16). An interaction between oBs and calcium supplements was suggested. Conclusions: The use of oBs increases specifically the odds of cardioembolic IS, in a duration-dependent manner, while leaves materially unaffected the odds of non-cardioembolic IS.